Assessing the Impact of Climate Change on Food Security in Pakistan: Challenges and Solutions (Journal of Interdisciplinary Insights, 2024)
Climate change presents a profound threat to global food security, with its impacts felt acutely in Pakistan—one of the most climate-vulnerable nations in the world. As a country where agriculture remains the backbone of the economy, providing livelihoods for a significant portion of the population, the consequences of climate change are severe. This paper delves into the intricate relationship between climate change and food insecurity in Pakistan, where rising temperatures, erratic rainfall patterns, and an increase in extreme weather events have compounded the already fragile agricultural system. The research explores how climate-induced factors, such as droughts, floods, and heatwaves, intensify food insecurity, particularly in rural areas reliant on agricultural production.The paper focuses on three key dimensions: agricultural water management, the impacts of climate-related disasters on crops and livestock, and the implementation of climate-smart agricultural practices. Firstly, the study investigates the water issues that plague Pakistan’s agricultural sector, including inefficient irrigation systems and depleting groundwater resources. Secondly, it examines the economic and social losses caused by repeated disasters, such as floods and droughts, which devastate crops and livestock, leaving millions at risk of hunger. Lastly, it highlights the role of climate-smart agriculture in mitigating these challenges by promoting practices that increase resilience and productivity under changing climate conditions.By synthesizing insights from reports, empirical data, and case studies from international organizations, government agencies, and academic research, the paper provides a comprehensive analysis of the multifaceted impacts of climate change on food security in Pakistan. The findings underscore the critical need for improved water management systems, investment in climate-resilient agricultural infrastructure, and the promotion of sustainable farming practices to ensure long-term food security in the face of climate adversity.Keywords
Keywords: Climate Change; Food Security; Agriculture; Water Management; Climate-Smart Agriculture